Existence of rhizobium bacteria on different types of legume plants in Kuala Pilah area / Hakeemah Mohamad Firdaus Tay - Mohamad Firdaus Tay, Hakeemah (2018)
The study of Rhizobium species was done in UiTM Cawangan Negeri Sembilan Campus Kuala Pilah, Negeri Sembilan during March until May of 2018. UiTM Cawangan Negeri Sembilan Campus Kuala Pilah located to the palm oil plantation which is the distance about 5 kilometers. Palm oil plantations have several environmental factors which is suitable for the life sustainability of legume plants. Rhizobium is the soil bacteria which have the ability to take out atmospheric nitrogen into a form available for plant use. Although many researches have been done but still many of us do not know the existence of Rhizobium inside the nodule of legume plants. So, the objective of this study is to indicate existence of Rhizobium in Calopogonium mucunoides and Centrosema pubescens based on their basic morphology. The method applied in this research is by visualizing the size and shape of Rhizobia under the microscope. The result obtained show that it is true that Rhizobium can be found in these two plants. Besides that, several test identification of Rhizobium has been done and the entire result show positive result. So, the study confirmed that Rhizobia can be found in the root nodules of these two types of plants.